Pemberian Motivasi serta Dampaknya Terhadap Kinerja Karyawan Pada Perusahaan Telekomunikasi Jakarta - Rani Kurniasari (Universitas Bina Sarana Informatika, 2018)
Every Company wants its employees to excel and work effectively. Thus need to be given motivation to encourage employee performance to increase. The type of motivation that can be given can be extrinsic and intrinsic motivation. With the encouragement to the subordinates is expected to generate the performance of employees can be maximized.The sample used for data collection in this study amounted to 50 (fifty) employees of telecommunication company in Jakarta. Likert scale used by writer to change qualitative data in questionnaire become quantitative data. The purpose of this study is to determine and analyze the magnitude of the influence of motivation on employee performance at one telecommunication company in South Jakarta which is engaged in the technology industry. The calculation of the questionnaire results using a simple linear regression formula. All of the author's calculations were assisted by the SPSS version 20 program released by IBM. Based on the analysis and data processing according to the calculation of correlation coefficient can be seen that the Motivation of Performance has a very strong relationship that is equal to 0.961 and according to the calculation of the coefficient of determination, can be known quite large is 92.3%, then influence Motivation on Performance can be seen through simple linear regression that is Y = 2,670 + 0,901X